Evaluation of a structural mechanics model to predict the effect of inserts in the bed support of chromatographic columns. (16th June 2015) - Gerontas, Spyridon; Lan, Tian; Micheletti, Martina; Titchener-Hooker, Nigel J.
Abstract: Cell culture titres are expected to increase still further over the forthcoming years. This imposes challenges for downstream processing including the potential need to use larger volumes of chromatography resins. Such a move could create throughput bottlenecks because of the compressible nature of many commercially available resins, which makes the operation of columns with diameters beyond 2 m infeasible due to resin collapse. The use of cylindrical inserts of negligible thickness has been proposed in the literature as a way to enhance the level of wall support, allowing higher superficial flow velocities to be applied and hence larger diameter columns to be used. In this study, a structural mechanics model has been developed to evaluate the effect of inserts on the column pressure drop and flow characteristics. Simulations were shown to be in good agreement with published experimental data. The model was then used to predict the effect of insert number, diameter, height and roughness on critical velocity of manufacturing scale columns. Highlights: Inserts are placed within chromatography columns to enhance wall support. The impact of column inserts is captured by structural mechanics models. Simulations are shown to be in good agreement with experimental data. The model helps selecting dimensions of inserts to increase column linear velocity.